Microbial community dynamics during composting of animal manures contaminated with arsenic, copper, and oxytetracycline - Ebrahim SHEHATA; Deng-miao CHENG; Qian-qian MA; Yan-li LI; Yuan-wang LIU; Yao FENG; Zhen-yu JI; Zhao-jun LI (Journal of Integrative Agriculture, 2021)
Effects of the heavy metal copper (Cu), the metalloid arsenic (As), and the antibiotic oxytetracycline (OTC) on bacterial community structure and diversity during cow and pig manure composting were investigated. Eight treatments were applied, four to each manure type, namely cow manure with: (1) no additives (control), (2) addition of heavy metal and metalloid, (3) addition of OTC and (4) addition of OTC with heavy metal and metalloid; and pig manure with: (5) no additives (control), (6) addition of heavy metal and metalloid, (7) addition of OTC and (8) addition of OTC with heavy metal and metalloid. After 35 days of composting, according to the alpha diversity indices, the combination treatment (OTC with heavy metal and metalloid) in pig manure was less harmful to microbial diversity than the control or heavy metal and metalloid treatments. In cow manure, the treatment with heavy metal and metalloid was the most harmful to the microbial community, followed by the combination and OTC treatments. The OTC and combination treatments had negative effects on the relative abundance of microbes in cow manure composts. The dominant phyla in both manure composts included Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria. The microbial diversity relative abundance transformation was dependent on the composting time. Redundancy analysis (RDA) revealed that environmental parameters had the most influence on the bacterial communities. In conclusion, the composting process is the most sustainable technology for reducing heavy metal and metalloid impacts and antibiotic contamination in cow and pig manure. The physicochemical property variations in the manures had a significant effect on the microbial community during the composting process. This study provides an improved understanding of bacterial community composition and its changes during the composting process.